Mesin Penyapu Jalan Manual - Aida Nurulhuda Kamalshah,; Eddy Ameerul Eiman Eddy Mismuliady,; Wan Anis Fatihah Wan Yushamshul,; Mohamed Nor, Mohd Hadri (Multidisciplinary Applied Research and Innovation, 2024)
Cleaning is a routine done by humans who care about the cleanliness of the environment. Among the cleaning tools that are often used to clean the road is a broom. Energy and time for the cleaning process using a regular broom takes a lot of time and energy. The alternative taken to deal with the problem is to build a manual road sweeper. Using full human power to sweep garbage would take a very long time and would be harmful to human health. This problem arises among road cleaning workers who take a long time to clean the road using only a broom. The garbage sweeper is designed to make the process of sweeping garbage faster and easier. The objective of the project is also to design a garbage sweeper that can transport a large load of garbage and produce a garbage sweeper that can save time and energy. The way to use this tool is very simple, that is, you only need to push the tool and point it at the place that only has rubbish. Next, the broom will rotate and all the rubbish can be swept and scooped into the bin. Indirectly, the process of cleaning junk can be done quickly and can reduce the human labour that only rejects these tools. In addition, the mechanical concept of this tool is the same as cycling. Where the sprocket drive (on the front tire) will rotate the driven sprocket (on the sweeper) using a chain (chain drive) that will rotate the sweeper according to the rotation of the front tire. The faster the front tire rotates, the faster the sweeper rotates. In conclusion, the design of this garbage sweeper can facilitate many private or government cleaning parties and is user-friendly who always use it for cleaning work.